2019
DOI: 10.1002/jmv.25574
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic burden of pre‐emptive therapy of cytomegalovirus infection in hospitalized allogeneic hematopoietic cell transplant recipients

Abstract: Cytomegalovirus (CMV) infection remains a major complication after allogeneic hematopoietic cell transplantation (allo-HCT). We conducted a retrospective study to determine the clinical and economic burden of pre-emptive therapy (PET) for CMV infection in 100 consecutive hospitalized adult CMV positive serostatus allo-HCT recipients and compared their hospitalization cost with allo-HCT recipients hospitalized with graft vs host disease without CMV infection (control group) and across 19 US cancer centers for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 41 publications
3
37
0
1
Order By: Relevance
“…In a single-institute study in the United States (US), pre-emptive therapy for CMV infection post-HSCT incurred an additional cost of US dollars (USD) 58,000-74,000 per patient for antiviral medication and longer hospital stays 23 . In another similar study, the cost of pre-emptive therapy for CMV infection was USD 116,976 per patient, compared with USD 12,496 per patient without CMV infection 25 . Besides the additional economic burden due to CMV infection and the need for pre-emptive therapy, higher mortality rates have been observed in allogenic HSCT patients with CMV viremia.…”
Section: Introductionmentioning
confidence: 93%
“…In a single-institute study in the United States (US), pre-emptive therapy for CMV infection post-HSCT incurred an additional cost of US dollars (USD) 58,000-74,000 per patient for antiviral medication and longer hospital stays 23 . In another similar study, the cost of pre-emptive therapy for CMV infection was USD 116,976 per patient, compared with USD 12,496 per patient without CMV infection 25 . Besides the additional economic burden due to CMV infection and the need for pre-emptive therapy, higher mortality rates have been observed in allogenic HSCT patients with CMV viremia.…”
Section: Introductionmentioning
confidence: 93%
“…Ueno et al report higher medical costs than those observed in our study, which is likely attributable to their cost analysis incorporating more components, including additional medications, blood products, and clinical examinations, whereas our study focused primarily on the antiviral agent, hospitalization, and adverse event management (eg, growth factor, dialysis). In a second study, El Haddad et al evaluated the comparative drug costs of GCV and FOS . El Haddad's evaluated a higher number of patients compared to ours and analyzed the cost per CMV episode, whereas our study evaluated the cost per patient and was restricted to the first reactivation episode.…”
Section: Discussionmentioning
confidence: 85%
“…We performed this pilot study due to the paucity of literature surrounding cost differences with the use of FOS or GCV for CMV infection. However, recently a multicenter study detailing cost of PET in CMV infection has been published that shows significant cost burden with PET . Another recent large retrospective database study investigating the clinical and economic burden of CMV management post‐alloHCT in Japan reported that CMV episodes post‐HCT are associated with significantly increased healthcare resource utilization .…”
Section: Introductionmentioning
confidence: 99%
“…CMV can also cause post-transplantation disease in recipients of allogeneic hematopoietic stem cell transplants, and pre-emptive therapy is often initiated after clinical evidence of CMV reactivation (prior to fulminant disease). The economic burden of this therapy is marked [ 58 ]. The mouse model of MCMV has been integral in the prediction of useful therapeutics for these clinical circumstances (reviewed in [ 59 ], with a discussion of the appropriate use for this model in reliably predicting human outcomes).…”
Section: Murine Cytomegalovirus Infection As a Model For Human Cytmentioning
confidence: 99%